Identification of a growth factor required for culturing specific fastidious oral bacteria. Issue 1 (1st January 2023) - Murugkar, Pallavi; Dimise, Eric; Stewart, Eric; Viala, Stéphane N.; Clardy, Jon; Dewhirst, Floyd E.; Lewis, Kim
ABSTRACT: Aims: The aim of this research was to isolate oral bacteria that are dependent for growth on adjacent bacteria producing a required growth factor and to identify the chemical structure of the growth factor. Methods: Porphyromonas pasteri strain KLE1280, could be cultivated with Staphylococcus hominis and Escherichia coli as helper strains. A deletion mutant library of E. coli was screened to determine genes involved in production of the growth factor. Compounds produced by the growth factor's pathway were screened to see if they would stimulate growth of strain P. pasteri KLE1280. The genomes of species related to P. pasteri KLE1280 were screened for presence of the factor's synthetic pathway. Results: Analysis of the E. coli deletion mutant library and growth studies identified 1, 2-dihydroxy-2-naphthoic acid (DHNA) and menaquinone-4 (MK4) as the growth factors. Strain P. pasteri KLE1280 was shown to lack five genes in the menaquinone synthesis pathway but to possess the two genes necessary to convert DHNA to menaquinone. Genome analysis found that 8 species in genera Porphyromonas and Tannerella lack five genes in the menaquinone synthesis pathway. Conclusions: Addition of DHNA to culture media allows isolation of strains of several oral species that are not recovered using standard media